2018
DOI: 10.1128/jcm.00761-17
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Nature of Double Alleles in Variable-Number Tandem-Repeat Patterns of More than 8,000 Mycobacterium tuberculosis Complex Isolates in The Netherlands

Abstract: Since 2004, variable-number tandem-repeat (VNTR) typing of Mycobacterium tuberculosis complex isolates has been applied on a structural basis in The Netherlands to study the epidemiology of tuberculosis (TB). Although this technique is faster and technically less demanding than the previously used restriction fragment length polymorphism (RFLP) typing, reproducibility remains a concern. In the period from 2004 to 2015, 8,532 isolates were subjected to VNTR typing in The Netherlands, with 186 (2.2%) of these ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The microevolution could also result in minor discrepancies between the experimental genotyping and WGS. Indeed, the most discrepant loci in our validation (QUB26 and QUB11b) were reported to be frequently associated with double alleles, a probable consequence of the microevolution ( Jajou et al, 2017 ). The accuracy of the genome assembly, which crucially depends on the read length, is also vital to the digital inference of the MIRU-VNTR profile.…”
Section: Discussionmentioning
confidence: 68%
“…The microevolution could also result in minor discrepancies between the experimental genotyping and WGS. Indeed, the most discrepant loci in our validation (QUB26 and QUB11b) were reported to be frequently associated with double alleles, a probable consequence of the microevolution ( Jajou et al, 2017 ). The accuracy of the genome assembly, which crucially depends on the read length, is also vital to the digital inference of the MIRU-VNTR profile.…”
Section: Discussionmentioning
confidence: 68%
“…Considering that the criteria necessary for identifying different types of M. tuberculosis polyclonal infections using IS6110-RFLP and MIRU-VNTR are well-defined, several studies were also found in the current review that reported on microevolution (Martín et al, 2007;Streit et al, 2015;Cohen et al, 2016;Jajou et al, 2018). The classification was not evident in some other reports that used IS6110-RFLP or MIRU-VNTR, due to results potentially indicating either an MSI or a microevolution event depending on the applied criteria (Al-Hajoj et al, 2010;Alves et al, 2011), or due to WGS not having a well-defined SNP threshold (Liu et al, 2015).…”
Section: Challenges Faced In Defining Msismentioning
confidence: 95%
“…This may be true but caution is warranted as routine culture often misses > 90% of viable cells [18]. Also, the observation that infections with double MIRU-VNTR bands are mixed infections that can be transmitted between patients [33] provides circumstantial evidence that new infections are often the result of larger numbers of mycobacterial cells that preserve some of the genetic diversity present in the source case. This preserved diversity within the infecting bacterial population may ultimately be useful to identify more details of transmission dynamics [8,33,39].…”
Section: The Regulation Of Latency and The Success Of Mtb Strainsmentioning
confidence: 99%
“…Also, the observation that infections with double MIRU-VNTR bands are mixed infections that can be transmitted between patients [33] provides circumstantial evidence that new infections are often the result of larger numbers of mycobacterial cells that preserve some of the genetic diversity present in the source case. This preserved diversity within the infecting bacterial population may ultimately be useful to identify more details of transmission dynamics [8,33,39]. Even more interestingly, it was recently observed that patients with a higher proportion of latent bacteria in their sputum appeared more likely to transmit the disease to close contacts [16].…”
Section: The Regulation Of Latency and The Success Of Mtb Strainsmentioning
confidence: 99%